UNIVERSAL DESIGN OF TRANSPORTATION SYSTEMS: A CASE STUDY OF ACCESS AND MOBILITY OF PEOPLE WITH DISABILITIES AT SELECTED INTERSECTIONS IN DAR ES SALAAM - Mushule, Nurdin K (Tanzania Journal of Engineering and Technology, 2018)
The pedestrian facilities at intersections must be usable by pedestrians of all ages and capabilities. Intersections in particular must be designed to safely accommodate pedestrians of all ages and physical and mental abilities. Often, however, intersection designs fail to accommodate people with visual and mobility disabilities. In this regard, for pedestrians with disabilities, intersections can prove to be a challenge. Some of those challenges include provision of insufficient pedestrian clearance time due to use of inappropriate design pedestrian speed. Most importantly, the required facilities to enable People With Disabilities (PWD) to use the intersection without hindrance may be missing. Obstacles such as uneven surfaces, unstable surfaces, nonexistent curb ramps, road crossings, changes in height of sidewalks, nonexistent guidance systems, obstructions, vegetation overhanging sidewalks, poles in the sidewalk, holes, etc. can all be remedied. This paper presents the results of the study which was carried out in Dar es Salaam to evaluate the extent to which the design of intersections satisfies the mobility and access needs of people with disabilities. The results indicate that the design of 20 major intersections in Dar es Salaam, mostly does not pay due attention to the needs of PWD.